Active Cancellation of the Tonal Component of Sound Using a Discrete Fourier Transform of Variable Length - Michał ŁUCZYNSKI; Andrzej DOBRUCKI; Stefan BRACHMAŃSKI (Archives of Acoustics, 2021)
The paper presents a method of eliminating the tonal component of an acoustic signal. The tonal component is approximated by a sinusoidal signal of a given amplitude and frequency. As the parameters of this component: amplitude, frequency and initial phase may be variable, it is important to detect these parameters in subsequent analysis time intervals (frames). If the detection of the parameters is correct, the elimination consists in adding a sinusoidal component with the detected amplitude and frequency to the signal, but the phase shifted by 180 degrees. The accuracy of the reduction depends on the accuracy of parameters detection and their changes.